2019
DOI: 10.1039/c9ra06614d
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted Article: Knockdown of long non-coding RNA OIP5-AS1 suppresses cell proliferation and migration in ox-LDL-induced human vascular smooth muscle cells (hVMSCs) through targeting miR-152-3p/PAPPA axis

Abstract: Knockdown of OIP5-AS1 suppressed ox-LDL-treated hVMSCs proliferation and migration; overexpression of miR-152 played the similar role of OIP5-AS1 knockdown; OIP5-AS1 functioned as ceRNA to regulate PAPPA expression through sponging miR-152.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…OIP5‐AS1 promotes apoptosis and inhibits proliferation in HUVECs treated with oxidative low‐density lipoprotein (ox‐LDL) 35 . Yang et al 36 similarly reported that OIP5‐AS1 promotes atherosclerosis in human vascular smooth muscle cells treated with ox‐LDL. Results from these two previous studies 35,36 implicate OIP5‐AS1 in atherosclerosis development.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…OIP5‐AS1 promotes apoptosis and inhibits proliferation in HUVECs treated with oxidative low‐density lipoprotein (ox‐LDL) 35 . Yang et al 36 similarly reported that OIP5‐AS1 promotes atherosclerosis in human vascular smooth muscle cells treated with ox‐LDL. Results from these two previous studies 35,36 implicate OIP5‐AS1 in atherosclerosis development.…”
Section: Discussionmentioning
confidence: 97%
“…Yang et al 36 similarly reported that OIP5‐AS1 promotes atherosclerosis in human vascular smooth muscle cells treated with ox‐LDL. Results from these two previous studies 35,36 implicate OIP5‐AS1 in atherosclerosis development. However, little was known about the role of OIP5‐AS1 in myocardial diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Zhang et al reported that miR-141 inhibited VSMCs proliferation by targeting PAPPA, implying PAPPA might play a momentous part in the pathogenesis of atherosclerosis [ 32 ]. In addition, Yang et al confirmed that PAPPA was upregulated in human vascular smooth muscle cells under ox-LDL administration [ 33 ]. In this study, PAPPA was elevated in HUVECs by treatment with ox-LDL.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have reported that, OIP5-AS1 is a ceRNA in Hepatoblastoma cells through modulating miR-186a-5p/ZEB1 [35] . For another example, OIP5-AS1 as ceRNA positively regulates PAPPA expression through the spongization of miRNA-152-3p [31] . Our research team reported that LncRNA OIP5-AS1 acted as a ceRNA to drive proliferation, invasion, migration and apoptosis of ovarian cancer cells via the spongization of miR-153-3p/KLF5 axis.…”
Section: Discussionmentioning
confidence: 99%